+0

# The value $$\left(\frac{1+\sqrt 3}{2\sqrt 2}+\frac{\sqrt 3-1}{2\sqrt 2}i\right)^{72}$$ is a positive real number. What real number is it?

+2
93
2
+518

The value
$$\left(\frac{1+\sqrt 3}{2\sqrt 2}+\frac{\sqrt 3-1}{2\sqrt 2}i\right)^{72}$$
is a positive real number. What real number is it?

michaelcai  Dec 14, 2017

#2
+81022
+1

We can write

[   (1 + sqrt (3)   +  sqrt (3)i  - 1i  ] ^72  / sqrt (8)^72  =

[  ( 1 - i)   +  (1 + i) sqrt(3) ] ^72  / sqrt (8) ^72  =

[ [ (1 - i)  + (1 + i)sqrt(3) ]^2 ] ^36 / [sqrt (8)^2]^36 =

[ [ (1 - i)  + (1 + i)sqrt(3)]^2 / sqrt (8)^2 ] ^36

Forget  about  the exponent of 36  for a second and look at this

[ (1 - i)   +  (1 + i) sqrt (3) ] ^2 / [sqrt (8)]^2  =

[ (1 - i)(1 - i)   +  2 (1 - i) (1 + i)sqrt (3)  +  (1 + i)(1 + i) *3 ]/8   =

[  - 2i  + 2 ( 2)sqrt (3)  + 2i * 3 ]/ 8    =

[ 4i + 4 sqrt (3) ]  =   [  4  (  i  +  sqrt (3) ) ]  / 8   =

(1/2)  [ sqrt (3)  + i ]

So.......we have

[ (1/2)^36]  *  [ sqrt (3)  + i ]^36    =   A

Looking at  the red part we can write this as

(2)^36  ( cos [36 (pi/6)]  + i sin [ 36 (pi/6) ] )  =

(2)^36  (  cos [ 6pi ]  +  i sin [6pi] )  =

(2)^36  [  1  +  0i ]  =

(2)^36

So  A   becomes

[ (1/2)^36 ] * 2^36  =  [ 2 / 2 ] ^36  =  1^36  =

1

CPhill  Dec 15, 2017
edited by CPhill  Dec 15, 2017
Sort:

#1
0

((1/2 + i/2) (sqrt(3) - i))/sqrt(2)=
Divide: 1 / 2 = 0.5
Divide: i / 2 = 0.5i
Square root: sqrt(3) = √ 3 = 1.7320508
Multiple: (0.5+0.5i) * (1.7320508-i) = 0.866025403784-0.5i+0.866025403784i+0.5 = 1.3660254+0.3660254i
alternative steps
0.7071068 × ei 45° × 2 × ei (-30°) = 0.707106781187 × 2 × ei (45°+(-30°)) = 1.4142136 × ei 15° = 1.3660254+0.3660254i
Square root: sqrt(2) = √ 2 = 1.4142136
Divide: (1.3660254+0.3660254i) / 1.4142136 = 0.9659258+0.258819i =(-1)^(1/12)
(-1)^(1/12)*72 =(-1)^6 =1

Guest Dec 14, 2017
#2
+81022
+1

We can write

[   (1 + sqrt (3)   +  sqrt (3)i  - 1i  ] ^72  / sqrt (8)^72  =

[  ( 1 - i)   +  (1 + i) sqrt(3) ] ^72  / sqrt (8) ^72  =

[ [ (1 - i)  + (1 + i)sqrt(3) ]^2 ] ^36 / [sqrt (8)^2]^36 =

[ [ (1 - i)  + (1 + i)sqrt(3)]^2 / sqrt (8)^2 ] ^36

Forget  about  the exponent of 36  for a second and look at this

[ (1 - i)   +  (1 + i) sqrt (3) ] ^2 / [sqrt (8)]^2  =

[ (1 - i)(1 - i)   +  2 (1 - i) (1 + i)sqrt (3)  +  (1 + i)(1 + i) *3 ]/8   =

[  - 2i  + 2 ( 2)sqrt (3)  + 2i * 3 ]/ 8    =

[ 4i + 4 sqrt (3) ]  =   [  4  (  i  +  sqrt (3) ) ]  / 8   =

(1/2)  [ sqrt (3)  + i ]

So.......we have

[ (1/2)^36]  *  [ sqrt (3)  + i ]^36    =   A

Looking at  the red part we can write this as

(2)^36  ( cos [36 (pi/6)]  + i sin [ 36 (pi/6) ] )  =

(2)^36  (  cos [ 6pi ]  +  i sin [6pi] )  =

(2)^36  [  1  +  0i ]  =

(2)^36

So  A   becomes

[ (1/2)^36 ] * 2^36  =  [ 2 / 2 ] ^36  =  1^36  =

1

CPhill  Dec 15, 2017
edited by CPhill  Dec 15, 2017

### 3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details